Mauritius : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
The empirical study shows that the equilibrium real exchange rate in Mauritius has been affected by the terms of trade, as well as by other fundamental determinants. It assesses the challenges posed to Mauritius's trade performance by the expiration of the preferential trade arrangements. It examines the empirical relationship among domestic prices, money, foreign prices, and the nominal exchange rate in Mauritius. The paper highlights Mauritius's inflation, monetary and exchange rate policies and instruments, and also presents and estimates a model for the determination of domestic prices.